Love of Money, Religiusitas, Machiavellian dan Persepsi Etis Auditor - Oktavia Ruwu, Eva; Sujana, I Ketut (E-Jurnal Akuntansi, 2023)
The research aims to analyze the effect of love of money, religiosity, Machiavellian on auditors' ethical perceptions. The population and sample of this study are auditors who work in Public Accounting Firms in the city of Denpasar, Bali. This study used a saturated sample technique with a large number of samples used, namely 47 respondents. The data analysis technique used is multiple linear regression analysis. The results of the study show that the love of money has a positive effect on the auditor's ethical perceptions. This shows that the higher the love of money, the lower the auditor's ethical perception. Religiosity has a positive effect on the auditor's ethical perceptions. This shows that the higher the religiosity, the higher the auditor's ethical perception. Machiavellian has a positive effect on the auditor's ethical perceptions. This shows that the higher the Machiavellian, the lower the auditor's ethical perception. Keywords: Auditor; Ethical Perception; Love Of Money; Machiavellian; Religiosity.